« Enseigner les passés douloureux en Europe : entre oubli et hypermnésie, quelle place pour l’enseignement ? » Présentation d’un projet européen de recherche - Stanislas HOMMET (E-REA)
Since the fall of the Berlin Wall, Europe as a space of identity has taken a "turn towards memory" and instances of unresolved histories have tended to multiply, unleashing mainly divisive forces in the process. Reading about painful pasts, also known as "live issues", raises questions as to the ultimate ends of the teaching of that particular History. The research project which is presented in this article brings together six partner countries whose purpose is to explore the historical conscience and perception of European teenagers. Can we apprehend the pasts that pass with difficulty in schools and, if so, in what forms and context ?